Behavior is movement only but how to interpret it? Problems and pitfalls in translational neuroscience—a 40-year experience - Lipp, Hans-Peter; Wolfer, David P. (Frontiers in Behavioral Neuroscience, 2022)
Translational research in behavioral neuroscience seeks causes and remedies for human mental health problems in animals, following leads imposed by clinical research in psychiatry. This endeavor faces several problems because scientists must read and interpret animal movements to represent human perceptions, mood and memory processes. Yet it is still not known how mammalian brains bundle all these processes into a highly compressed motor output in the brain stem and spinal cord, but without that knowledge translational research remains aimless. Based on some four decades of experience in the field, the paper identifies sources of interpretation problems and illustrates typical translational pitfalls. 1) The sensory world of mice is different. Smell, hearing and tactile whisker sensations dominate in rodents, while visual input is comparatively small. In humans, the relations are reversed. 2) Mouse and human brains are equated inappropriately: association cortex makes up a large portion of the human neocortex while it is relatively small in rodents. The predominant associative cortex in rodents is the hippocampus itself, orchestrating chiefly inputs from secondary sensorimotor areas and generating species-typical motor patterns that are not easily reconciled with putative human hippocampal functions. 3) Translational interpretation of studies of memory or emotionality often neglect the ecology of mice, an extremely small species surviving by freezing or flight reactions that do not need much cognitive processing. 4) Further misinterpretations arise from confounding neuronal properties with system properties, and from rigid mechanistic thinking unaware that many experimentally induced changes in the brain do partially reflect unpredictable compensatory plasticity. 5) Based on observing hippocampal lesion effects in mice indoors and outdoors, the paper offers a simplistic general model of hippocampal functions in relation to hypothalamic input and output, placing hypothalamus and the supraspinal motor system at the top of a cerebral hierarchy. 6) Many translational problems could be avoided by inclusion of simple species-typical behaviors as end-points comparable to human cognitive or executive processing, and to rely more on artificial intelligence for recognizing patterns not classifiable by traditional psychological concepts.